Central Events and Causal Connections: A Narrative Inquiry-Study among Colombian Female Scholars in their Processes as writers - Ramos-Holguín, Bertha; Peñaloza-Rallón, Anna Carolina (GIST – Education and Learning Research Journal, 2020)
In the Colombian context there has been an increase in the interest for publishing in high impact academic journals. This is due to various factors such as institutional requirements, hiring requirements, categorization of teachers and academic visibility. The purpose of this research-based paper, as a decolonial report, is to portray the central events and the causal connections of three female Colombian authors in their process as writers for academic purposes. Data were gathered through in-depth interviews that emphasized on Van Manen's (1997) four lifeworld existential dimensions that include lived time, lived space, lived body, and lived relation. These dimensions helped us uncover the essences of lived experience. Results indicated that central events and causal connections affect the authors’ experiences in their process as writers. The key ingredients female authors judge as important events were social interactions with mentors and the context.